2021
DOI: 10.29203/ka.2021.506
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of myxomycetes in Turrialba, Costa Rica

Abstract: Long-term monitoring and phenological patterns of microbial communities are rare in the scientific literature. Myxomycetes have life cycle characteristics that allow both to be documented. The present study summarizes the integrated floristic and bioclimatic components of a 30-month assessment of myxomycete sporocarps in a premontane tropical forest in Turrialba, Costa Rica. Based on monthly visits and a standard sampling effort of 120 minutes per visit, myxomycetes were recorded on leaves, twigs, and logs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Field research on myxomycetes has shown that quick climatic changes, such as rapid freezing (Schnittler et al 2015) or sudden precipitation (Rojas et al 2021b) negatively affect the production of fruiting bodies in field conditions. In a similar manner, the results presented herein suggest that a rapid increment in temperature, albeit for a short period of time, might have the opposite effect but in moist chamber situations.…”
Section: Discussionmentioning
confidence: 99%
“…Field research on myxomycetes has shown that quick climatic changes, such as rapid freezing (Schnittler et al 2015) or sudden precipitation (Rojas et al 2021b) negatively affect the production of fruiting bodies in field conditions. In a similar manner, the results presented herein suggest that a rapid increment in temperature, albeit for a short period of time, might have the opposite effect but in moist chamber situations.…”
Section: Discussionmentioning
confidence: 99%
“…Physarum polycephalum offers the possibility to consider both chronological and replicative time simultaneously. During its development, the zygote undergoes synchronous mitotic divisions every 8-12 h but without cytokinesis to form a single multi-nucleated cell, called a plasmodium [59,60]. Hence, the cell grows over time but there is no cell division.…”
Section: Introductionmentioning
confidence: 99%